CUL3 (cullin 3)-mediated ubiquitination and degradation of BECN1 (beclin 1) inhibit autophagy and promote tumor progression. Issue 12 (2nd December 2021) - Li, Xuan; Yang, Kai-Bin; Chen, Wei; Mai, Jia; Wu, Xiao-Qi; Sun, Ting; Wu, Rui-Yan; Jiao, Lin; Li, Dan-Dan; Ji, Jiao; Zhang, Hai-Liang; Yu, Yan; et al.
ABSTRACT: Macroautophagy/autophagy plays an important role during the development of human cancer. BECN1 (beclin 1), a core player in autophagy regulation, is downregulated in many kinds of malignancy. The underlying mechanism, however, has not been fully illuminated. Here, we found that CUL3 (cullin 3), an E3 ubiquitin ligase, could interact with BECN1 and promote the K48-linked ubiquitination and degradation of this protein; In addition, CUL3 led to a decrease in autophagic activity through downregulating BECN1. We also found that KLHL38 was a substrate adaptor of the CUL3 E3 ligase complex-mediated ubiquitination and degradation of BECN1. In breast and ovarian cancer, CUL3 could promote the proliferation of tumor cells, and the expression of CUL3 was related to poor prognosis in patients. Our study reveals the underlying mechanism of BECN1 ubiquitination and degradation that affects autophagic activity and subsequently leads to tumor progression, providing a novel therapeutic strategy that regulates autophagy to combat cancer. Abbreviations : ATG: autophagy-related BECN1: beclin 1 CHX: cycloheximide CoIP: co-immunoprecipitation CUL3: cullin 3 IP: immunoprecipitation MS: mass spectrometry PtdIns3K: phosphatidylinositol 3-kinase UPS: ubiquitin-proteasome system